Strings and wind based music instruments recognition - Kerk, Swat Lian, 1989-, author; Md. Sah Salam, supervisor; Fakulti Komputeran (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper (Sarjana Muda Sains Komputer (Perisian Grafik & Multimedia)) - Universiti Teknologi Malaysia, 2012